2019
DOI: 10.3390/md17010039
|View full text |Cite
|
Sign up to set email alerts
|

Differences between Motile and Nonmotile Cells of Haematococcus pluvialis in the Production of Astaxanthin at Different Light Intensities

Abstract: Haematococcus pluvialis, as the best natural resource of astaxanthin, is widely used in nutraceuticals, aquaculture, and cosmetic industries. The purpose of this work was to compare the differences in astaxanthin accumulation between motile and nonmotile cells of H. pluvialis and to determine the relationship between the two cells and astaxanthin production. The experiment design was achieved by two different types of H. pluvialis cell and three different light intensities for an eight day induction period. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 44 publications
(72 reference statements)
1
13
0
1
Order By: Relevance
“…Additionally, the growth of 4x culture under SS rapidly declined upon the provision of continuous illumination, despite the similar variation of biomass concentration under CS and SS up to day 28. This could have occurred due to the presence of vegetative cells which were sensitive to high light stress [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…Additionally, the growth of 4x culture under SS rapidly declined upon the provision of continuous illumination, despite the similar variation of biomass concentration under CS and SS up to day 28. This could have occurred due to the presence of vegetative cells which were sensitive to high light stress [ 55 ].…”
Section: Resultsmentioning
confidence: 99%
“…This is supported by previous researches that the motile cells of H. pluvialis were more susceptible than nonmotile cells to photooxidative stress and easy to die under the high light conditions [ 23 , 32 ]. In addition, our recent work indicated that nonmotile cells had a stronger astaxanthin accumulation capacity than motile cells [ 33 ]. During the encystment, the nonmotile cells have accumulated a certain amount of lipids and carbohydrates which play important roles in the synthesis of astaxanthin [ 10 , 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that upon exposure to low temperature (4 °C) Haematococcus predominantly exists in the non-motile palmella stage (e.g., as reported previously for an arctic strain by Klochkova et al [29]). Non-flagellate green palmella stages of Haematococcus have a stronger tolerance to photooxidative stress [30] and could be more resistant to cell immobilization and/or may transform more successfully into akinetes. Longer storage times (>24 h) of the initial biomass, however, led to decreased biomass and astaxanthin productivities on TL-PSBRs presumably because of increased rates of cell death in the highly concentrated suspension.…”
Section: Discussionmentioning
confidence: 99%